2016
DOI: 10.1088/0953-2048/29/4/045010
|View full text |Cite
|
Sign up to set email alerts
|

A study of the electromagnetic characteristics of no-insulation GdBCO racetrack coils under an external magnetic ripple field

Abstract: Here we report the effect of an external magnetic ripple field on the electromagnetic characteristics of GdBCO racetrack coils being operated with a constant DC current. Two types of GdBCO racetrack coils, one wound without turn-to-turn insulation (NI) and the other wound with Kapton tape (INS), were examined under external ripple fields generated by a permanent magnet mounted on a rotor, which was driven by a separate AC motor. The voltage fluctuations and magnetic field variations were measured with respect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…The temporal variation of the magnetic field generated by the coils themselves was investigated in a number of studies, although AC loss was not analyzed in detail [7,[19][20][21][22][23]. Kim et al measured the AC loss with an applied AC current [24] and found that the no-insulation coils had lower AC loss than their insulated counterparts because the turn-to-turn contacts create a bypass for the applied current.…”
Section: Introductionmentioning
confidence: 99%
“…The temporal variation of the magnetic field generated by the coils themselves was investigated in a number of studies, although AC loss was not analyzed in detail [7,[19][20][21][22][23]. Kim et al measured the AC loss with an applied AC current [24] and found that the no-insulation coils had lower AC loss than their insulated counterparts because the turn-to-turn contacts create a bypass for the applied current.…”
Section: Introductionmentioning
confidence: 99%
“…The no-insulation (NI) winding technique [24] provides HTS coils with better thermal stability [25,26], higher current density [27,28], defect-irrelevance properties [29,30] and better mechanical integrity [31][32][33][34][35]. In recent years, the NI winding technique has facilitated quite a few breakthroughs in HTS magnet technology [28,36].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have studied the inductive voltages of NI coils caused by their electromagnetic induction with external AC magnets [20][21][22], resistive voltages of NI coils with the observation of a local thermal quench under time-varying fields [5,23,24] and the critical current degradation of NI coils caused by an axial AC field [5,25]. However, the unique behaviors of NI magnets affected by the dynamic resistance have not yet been clearly observed.…”
Section: Introductionmentioning
confidence: 99%